Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada UPTD Puskesmas Lubuk Alung - Yani, Putri; Sari, Marta Widian; Sari, Yosi Puspita (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to determine and analyze the influence of leadership style and organizational culture on employee performance, both directly and indirectly through job satisfaction as an intervening variable at UPTD Puskesmas Lubuk Alung, Padang Pariaman Regency. This research employs a quantitative method with a causal associative approach. The population in this study were all employees of UPTD Puskesmas Lubuk Alung, totaling 55 people. Due to the small population size, the sampling technique used was saturated sampling (census), where the entire population served as respondents. Data collection was conducted through questionnaires using a Likert scale. The data analysis technique used was Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS 3.0 software.The results of this study indicate that: (1) Leadership style and organizational culture have a positive and significant effect on job satisfaction; (2) Job satisfaction has a positive and significant effect on employee performance; (3) Directly, leadership style and organizational culture have a negative and insignificant effect on employee performance; (4) However, indirectly, leadership style and organizational culture have a positive and significant effect on employee performance through job satisfaction as an intervening variable. These findings demonstrate that leadership style and organizational culture do not directly improve performance but are effective when mediated by employee job satisfaction .